Cultural revivalism in Israel and China: imagining lives against the present - Becke, Johannes; Kurtz, Joachim (The journal of transcultural studies, 2023)
Cultural revivalists, ranging from adherents of political Islam and contemporary Chinese New Confucians to Hindu nationalists and Israel’s messianic right, raise a broad spectrum of nativist claims to resurrect premodern and precolonial authenticity. All revivalist movements portray their cause as an existential revolt against assimilation. At the same time, their fascination for their perceived enemy cultures—imaginary versions of the global “West” or local adversaries—reveals deep-seated ambivalences. In their struggle for ethno-cultural survival, the search for best practices of self-assertion focuses almost obsessively on immediate and imagined antagonists. To capture the ambivalences of these contradictory impulses and theorize the transcultural nature of this specific kind of enmity, this article connects and compares two different movements of contemporary cultural revivalism: Temple activism in Israel and Political Confucianism in mainland China. The two case studies show that cultural revivalists not only mimic the organizational templates of other radical movements that imagine lifestyles and forms of society embodying the pristine and enchanted ways of a world before the advent of a depraved “Western” modernity. To reach their goals, they also engage in systematic learning from the enemy. As a result, cultural revivalists are deeply entangled with their declared enemies in terms of behavioral patterns, ideological tropes, or religious practices. The article argues that this insight could be applied more broadly to the fields of enmity and transcultural studies: If enmity provokes mutual learning, to the point of producing what we may call “mimetic isomorphism,” it must be considered as a central driver of transculturation.
Gesehen am 04.06.2024